Penggunaan Media Pembelajaran Motion Graphic Mengakibatkan Perbedaan Motivasi dan Hasil Belajar Kognitif Siswa Secara Parsial dan Simultan pada Materi Sistem Gerak Kelas XI - Wardani, Ida Ayu Nova Intan; Sutajaya, I Made; Syah, Moh Jafron (Jurnal Pendidikan Biologi Undiksha, 2025)
This study investigates the impact of motion graphic learning media on the motivation and cognitive learning outcomes of students in class XI, focusing on movement system material. Employing a quasi-experimental design, this research utilizes a non-equivalent pre and post-test control group design. The study population comprised all classes at SMA Negeri 1 Bangli, with class XI MIPA 1 (30 students) serving as the control group and class XI MIPA 2 (30 students) as the experimental group. Simple random sampling was used to select the samples. Data on learning motivation were collected through a Likert scale questionnaire, while cognitive learning outcomes were assessed via evaluation tests. The data were analyzed using descriptive statistics and hypothesis testing with the Manova Test. The findings revealed that the use of motion graphic media did not affect student motivation. The results of the research show that: (1) the use of motion graphic learning media does not result in differences in student motivation in class (2) The use of motion graphic learning media results in differences in students' cognitive learning outcomes in class XI movement sistems material. because the contribution is quite high, namely 31,8% and in the experimental class it is 43,9% higher compared to the control class. (3) The use of motion graphic learning media resulted in differences in motivation and cognitive learning outcomes of students simultaneously on the material of the motion system of class XI and the contribution of motivation and learning outcomes simultaneously amounted to 32.8% compared to the control class. In conclusion, while motion graphic learning media did not influence student motivation, it significantly enhanced cognitive learning outcomes and, when combined with motivation, showed notable differences compared to the control class.